2022
DOI: 10.1002/lt.26488
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of primary percutaneous stent angioplasty for pediatric posttransplantation portal vein stenosis

Abstract: This study aims to evaluate the long-term efficacy and reintervention rate after primary percutaneous portal vein stent angioplasty for portal vein stenosis (PVS) in pediatric liver transplantation (LT) recipients. From 2004 to 2020, a total of 470 pediatric LTs were performed in our center. All cases were screened for interventional PVS treatment and analyzed retrospectively. We identified 44 patients with 46 percutaneous angioplasties for posttransplantation PVS. The median interval from LT to percutaneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
5
0
3
Order By: Relevance
“…Interventional treatment for PV complications is much more difficult in pediatric than in adult LT recipients because pediatric patients have smaller PVs, and because their physical growth is ongoing [11][12][13][14][15]. Thus, the use of cryopreserved iliac veins is generally not recommended for pediatric LT.…”
Section: Introductionmentioning
confidence: 99%
“…Interventional treatment for PV complications is much more difficult in pediatric than in adult LT recipients because pediatric patients have smaller PVs, and because their physical growth is ongoing [11][12][13][14][15]. Thus, the use of cryopreserved iliac veins is generally not recommended for pediatric LT.…”
Section: Introductionmentioning
confidence: 99%
“…
To the editor,The paper by Bukova et al [1] that was published on liver transplantation dangerously questions the possibility of effectively treating portal vein stenosis after pediatric liver transplantation without the need for primary stenting. In a retrospective cohort of a total of 470 pediatric liver transplants performed in a single center from 2004 to 2020, they reported very positive outcomes with a mean follow-up of 5.7 years and they concluded that primary stent angioplasty should be considered as first-line treatment for portal vein stenosis after pediatric LT.In our opinion, this data must be considered with caution in pediatric patients who have a much longer life expectancy after liver transplantation.
…”
mentioning
confidence: 99%
“…Não existe consenso na literatura em relação ao melhor protocolo de anticoagulação e/ou antigregação após a RVP em crianças (21,28,37,54) . Porém, seu uso está associado a menor recorrência da estenose/trombose venosa portal (54) .…”
Section: Discussionunclassified
“…O sucesso técnico tardio foi avaliado pelo tempo entre o procedimento e a recidiva (estenose/trombose) com necessidade de nova intervenção. Este, por sua vez, pode ser dividido em (21,43) : a) Perviedade primária -porcentagem de stents pérvios, sem necessidade de procedimento adicional, durante período de seguimento; b) Perviedade primária assistida -porcentagem de stents pérvios após intervenção para manutenção da sua perviedade devido a estenose da VP (intrastent ou nas margens proximal ou distal); c) Perviedade secundária -porcentagem de stents pérvios após intervenção para manutenção da sua perviedade devido a nova TVP.…”
Section: Sucesso Técnicounclassified
See 1 more Smart Citation